Mechanical properties and dynamic mechanical analysis of thermoplastic-natural-rubber-reinforced short carbon fiber and kenaf fiber hybrid composites - Anuar, Hazleen; Hj J Ahmad, Sahrim; Rasid, Rozaidi; Ahmad, Azizan; Wan Busu, W. N. (John Wiley and Sons Inc.., 2008)
The hybridization of thermoplastic natural rubber based on carbon fiber (CF) and kenaf fiber (KF) was investigated for its mechanical and thermal properties. Hybrid composites were fabricated with a melt-blending method in an internal mixer. Samples with overall fiber contents of 5, 10, 15, and 20 vol % were subjected to flexural testing, and samples with up to 30% fiber content were subjected to impact testing. For flexural testing, generally, the strength and modulus increased up to 15 vol % and then declined. However, for impact testing, higher fiber contents resulted in an increment in strength in both treated and untreated composites. Thermal analysis was carried out by means of dynamic mechanical analysis on composites with 15 vol % fiber content with fractions of CF to KF of 100/0, 70/30, 50/50, 30/70, and 0/100. Generally, the storage modulus, loss modulus, and tan d for the untreated hybrid composite were more consistent and better than those of the treated hybrid composites. The glasstransition temperature of the treated hybrid composite was slightly lower than that of the untreated composite, which indicated poor damping properties. A scanning electron micrograph of the fracture surface of the treated hybrid composite gave insight into the damping characteristics.